Asked by | 25th May, 2010, 01:25: PM
Let X be the man's present age, and Y, Z be the two sons present ages respectively.
X = 5(Y + Z) .
Hence Y + Z = X/5. ..... (1)
After 5 Years the ages will all be increased by 5.
X + 5 = 2(Y + 5 + Z + 5).
X + 5 = 2(Y + Z + 10)
But Y + Z = X/5 from (1)
X + 5 = 2(X/5 + 10)
X - 2X/5 = 15.
3X = 15x5
X = 25 years,
The man's present age is 25 years.
Answered by | 25th May, 2010, 06:29: PM
Kindly Sign up for a personalised experience
- Ask Study Doubts
- Sample Papers
- Past Year Papers
- Textbook Solutions
Verify mobile number
Enter the OTP sent to your number